The Use of a Learning Management System (LMS) to Serve as the Virtual Common Space of a Network for the Scholarship of Teaching and Learning (SoTL) in an Academic Department - Scott Merrett; Kerry Ritchie; Genevieve Newton; Lorraine Jadeski; Nicolette Bradley; William Bettger (MDPI AG, 2013)
Traditionally, undergraduate curriculum committees, consisting of appointed faculty and student representatives, have served as the sole departmental vehicle for investigating, discussing and promoting the scholarship of teaching and learning (SoTL) within an academic department. However, with the universal demand for greater accountability on all aspects of evidence-based teaching and on the totality of student learning and career outcomes, some academic departments have encouraged the formation of additional organizations to support their SoTL mandate. In the Department of Human Health and Nutritional Sciences, the approach taken was to combine the interests of the faculty who had a sustained interest in the "scholarship of knowledge translation and transfer" in the health sciences with those who had a developing interest in SoTL. These faculty members would then form the foundation of a "network" which has been called the K*T3net. The virtual common space of the network is on a Learning Management System (LMS) site which is accessed by all faculty members in the network and by a growing number of staff and senior PhD students in the department. The features and potential uses of the K*T3net website will be discussed. The development of the K*T3net has already supported the proposal for a new undergraduate course on SoTL and is opening the possibility for graduate students to add a SoTL component to their thesis research.